Perforated second trimester appendicitis with abdominal compartment syndrome managed with negative pressure wound therapy and open abdomen - Turnock, Adam R. (J Surg Case Rep, 2016)
Abdominal compartment syndrome (ACS) is a known complication of laparotomy; however, the literature is lacking in regards to treatment of this entity in pregnant patients. We present a case of acute perforated appendicitis in a second trimester primagravida, complicated by gangrenous necrosis of the contiguous bowel with subsequent development of ACS and intra-abdominal sepsis. This was treated with a novel approach, using non-commercial negative pressure wound therapy and open abdomen technique. Gestational integrity was preserved and the patient went on to experience a normal spontaneous vaginal delivery. At 5 years post-delivery the patient has had no surgical complications and her baby has met all developmental milestones.